Zadanie 1.
[tex](1.2)^{-2} = (\frac{1}{1.2})^{2} = \frac{1}{1.44}[/tex]
[tex]16^{-1} = (\frac{1}{16})^{1} = \frac{1}{16}[/tex]
[tex](1\frac{1}{6})^{-2} = (\frac{7}{6})^{-2} = (\frac{6}{7})^{2} = \frac{36}{49}[/tex]
[tex](6\sqrt{3} )^{-2} = (\frac{1}{6\sqrt{3}})^{2}=(\frac{1}{6^{2} \cdot(\sqrt{3})^{2}})=(\frac{1}{36\cdot 3})=\frac{1}{108}[/tex]
Zadanie 2.
[tex]a) (8^{-1} - 4^{-2})^{-1} = (\frac{1}{8} -(\frac{1}{4})^{2})^{-1} = (\frac{2}{16} -\frac{1}{16})^{-1}= (\frac{1}{16})^{-1} = 16[/tex]
[tex]b) 24\cdot 2^{-3} - 32\cdot 4^{-2} = 24\cdot (\frac{1}{2})^{3} - 32 \cdot (\frac{1}{4})^{2} = 24 \cdot \frac{1}{8} - 32 \cdot \frac{1}{16} = 3 - 2 = 1[/tex]